Main Currents in Nineteenth Century Literature - 2. The Romantic School in Germany - Brandes, Georg, 1842-1927; Morison, Mary; White, Diana (Translator), 1868-1950 (Salt Lake City, UT : Project Gutenberg, 2014)
"Main Currents in Nineteenth Century Literature - 2. The Romantic School in Germany" by George Brandes is a scholarly work written in the early 20th century. The book explores the German Romantic School, delving into its key figures and literary movements, and provides a critical analysis of how these works relate to broader social and psychological themes. Brandes aims to connect literature with the historical and emotional context from which it emerged, guiding readers through the complexities of Romanticism. The opening of the text presents an introduction to the German Romantic School, highlighting the challenges faced by a foreign critic attempting to outline its vastness. Brandes reflects on his position as a Dane, recognizing the depth of knowledge inherent to native scholars while seeking to offer a unique perspective. He sets forth his intention to illuminate the connections between literature and life, paying particular attention to the emotional undercurrents that define this literary movement. Brandes emphasizes that German Romanticism, while a reaction to preceding literary traditions, simultaneously encompasses rich, diverse, and innovative expressions of individuality and psychological depth, a theme that will be further examined in subsequent sections of the work. (This is an automatically generated summary.)
The pioneers of Romanticism -- Hölderlin -- A. W. Schlegel -- Tieck and Jean Paul -- Social endeavours of the Romanticists: Lucinde -- Romantic purposelessness -- "Lucinde" in real life -- Schleiermacher's letters -- Wackenroder: Romanticism and music -- Attitude of Romanticism to art and nature -- Romantic duplication and psychology -- Romantic soul. Novalis -- Longing: "The blue flower" -- Arnim and Brentano -- Mysticism in the Romantic drama -- Romantic literature and politics -- Romantic politicians.
Release date is 2014-12-26
E-text prepared by Marc D'Hooghe (http://www.freeliterature.org) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Literature, Modern -- 19th century -- History and criticism; Naturalism in literature; Romanticism